Impact of Ammonia During Composting on Calonectria pseudonaviculata and C. henricotiae, Causal Agents of Boxwood Blight. Issue 2 (3rd April 2019) - Harvey, Robert J.; Shishkoff, Nina; Pecchia, John A.; Davis, Donald D.
Abstract: Boxwood ( Buxus spp.) blight is a devastating disease caused by the Ascomycete fungus Calonectria pseudonaviculata in the U.S. and Europe. A second Calonectria species, C. henricotiae, is also pathogenic on boxwood in Europe, but is not present in the U.S. where it is classified as a quarantine pathogen. Composting can eradicate various plant pathogens and high temperature is likely the most important factor influencing pathogen eradication. We previously reported that C. pseudonaviculata microsclerotia survived exposure to 40 °C in an incubator without compost, whereas exposure to the same temperature and time, but with compost added, greatly decreased survival. That is, the decrease in Calonectria growth and survival in compost was greater than could be accounted for by high temperature alone. We hypothesized that the enhanced decrease in Calonectria growth and survival might be due to ammonia, a fungitoxic gas produced during composting. In this laboratory study, we determined that ammonia within agar in Petri plates reduced radial growth of both C. pseudonaviculata and C. henricotiae . In studies with C. pseudonaviculata, gaseous ammonia reduced microsclerotia survival. Our findings suggest that composting dead or dying blighted boxwoods in the presence of ammonia could reduce dissemination of both Calonectria species from blighted to healthy boxwoods.